South African landscape painting, 1848-2008 : a handbook for teachers - Newham, Priska (Department of Historical Studies, 2015)
My dissertation looks at South African landscape painting with the requirements of high school art teachers in mind. It has been written in consultation with Professor Michael Godby, at the University of Cape Town, the curator of the landscape exhibition, to be held at the Old Town House in Cape Town from 9 June to 11 September 2010. The handbook is designed to be distributed to educators at the Ibhabhathane Project Workshop organised to coincide with the exhibition. This is a teaching resource for Visual Culture Studies for Grades 10 to 12. It focuses on an analysis of artists in the school curriculum who have engaged with the genre in diverse and interesting ways.